Model Kepemimpinan Pendidikan Kontingensial Dan Situasional Dalam Meningkatkan Efektivitas Organisasi Sekolah - Asep Marfu; Nursaidah; Syifa Fauziah El Abida; Encep Syarifudin; Mahdum (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
This study aims to analyze contingency and situational educational leadership models in enhancing the effectiveness of school organizations. The selection of this topic is based on the crucial role of leadership in determining the success of educational organizations in achieving their goals. School principals, as educational leaders, are required to be able to adjust their leadership styles to the conditions, characteristics of teachers and educational staff, and the dynamic situations within schools. The contingency approach emphasizes that leadership effectiveness depends on the alignment between leadership style and the situation encountered, while the situational approach requires leaders to be flexible in regulating strategies and leadership styles according to the level of readiness of their subordinates. This study employs a descriptive qualitative method, with data collected through interviews, observations, and documentation studies involving principals and teachers in several vocational high schools. The findings indicate that the implementation of contingency and situational leadership models can improve school organizational effectiveness through enhanced teacher performance, harmonious communication, and appropriate decision-making. Furthermore, the flexibility and adaptability of school principals in responding to changes in the school environment are key factors in creating a productive and collaborative working climate. In conclusion, contingency and situational leadership models make a significant contribution to shaping effective school organizations that are responsive to change and oriented toward continuous improvement in educational quality